Reexamining the Publicness of Zakat Governed by BAZNAS in Jember Regency - Dayar, Mohammad Baladdudin; Khotimah, Khusnul; Adisiswanto, Alissa Ernawati (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2026)
This study analyses how publicness is manifested in the administration of zakat by BAZNAS in Jember Regency, as well as its implications for the creation of public value in poverty alleviation programmes.. The role of Baznas is worthy of being studied in the context of this problem because, as the manager of the National Zakat Agency (BAZNAS), it has a strategic role in community economic empowerment through zakat, infaq, and alms-based assistance programs with the hope of being able to create sustainable independence in the long term through community empowerment programs. This study employs a qualitative case study design. Data were collected between March and November 2025 through in-depth interviews with six informants representing BAZNAS management/staff, UPZ partners, local stakeholders, and beneficiaries, supplemented by document analysis (programme SOPs, half-yearly/annual reports, and monitoring documents). Analysis was conducted using thematic coding to examine four dimensions of public engagement: public mandate and coordination, participation in decision-making, accountability and transparency, and empowerment outcomes. The results of this study show The findings indicate that public engagement is uneven: formal mandates and digital reporting innovations enhance information transparency, yet programme decision-making processes tend to be top-down and the participation of beneficiaries in programme design remains limited. Productive zakat programmes (business capital, Z-Mart, Z-Chicken) demonstrate an empowerment orientation, but evidence of sustainability (mentoring, changes in income, and the transition from beneficiaries to donors) has not yet been systematically documented. This study contributes by offering a set of NPG-based transparency indicators to assess zakat governance in hybrid organisations.